Towards a Model of Designing an Organizational Structure in a Knowledge Based Society - Mihai Vărzaru; Eric Jolivet (Amfiteatru Economic Journal, 2011)
The role of the manager in the knowledge society is to lead, in a productive and cost effective manner, a system that is at the crossroads of three worlds: the environment, the human and the organization. To ensure the continuity of the organization, the manager must choose an appropriate structure that would enable it to increase productivity, improve quality of goods and maintain the motivation, satisfaction and involvement of the human factor. Changes promoted by the influences of organizational theories and knowledge management have resulted in reducing the emergence of hierarchical levels, formal control, in a low degree of formalization in general and in the emergence of deconstructed forms. The concept of organizational design is promoted by structuring the organization and seeks to ensure consistency among strategy, structure and incentive systems of the organization, an idea which also represents the basis of the organizational perspective imposed by Mintzberg(1990). This paper builds upon the three main theories that have influenced the design of organizational structure and proposes an integrated model that takes into account the changes promoted by knowledge management and aims at satisfying human resources quantification.
Keywords: M12; 330; structure; organizational design; knowledge management; contingency; model; approach